Pharmacy Phamilies as a Component of a Co-Curricular Program for Doctor of Pharmacy Students - Nancy Mason; Jacqueline Dela Pena; Bianca Campbell; Burgunda Sweet (University of Minnesota Libraries Publishing, 2020)
Background: Pharmacy student professional growth depends heavily on co-curricular involvement, in addition to classroom learning.  Co-curricular programming can be supported by an innovative structure using self-directed learning and a unique mentorship process.  Innovation: A novel faculty and peer mentorship structure, called Pharmacy Phamilies, is integrated into a credited Lifelong Learning course that spans the 4 years of our PharmD program.  This course is comprised of student-chosen activities to meet requirements in six domains, as well as reflections and other assignments.  Recent changes include a new Pharmacy Phamily group reflection process and the use of co-curricular logs to document student activities. Findings: Based on a student survey, the majority of respondents were satisfied with their level of engagement with their Pharmacy Phamily (72%) and with their advisor (76%).  The majority also reported that the Pharmacy Phamily program is meeting its goals of establishing a sense of community at the college (76%) and enhancing students' professional development (72%).  A total of 86% of students preferred the Pharmacy Phamily group reflection over the former six individual reflections and 93% of students agreed the co-curricular log was a useful tool to document involvement in professional activities. Conclusion: Pharmacy Phamilies and peer-reviewed, group reflection can provide an inclusive structure of support and social connection for students at the college of pharmacy.